pengaruh model TGT dengan media kartu bergambar terhadap aktivitas belajar dan penguasaan materi oleh siswa - ENJELINA - HUTASOIT; Darlen Sikumbang; Rini Rita T Marpaung (Universitas Lampung, 2013)
The results of observation with X grades’ biology teacher of Persada Senior High School Bandar Lampung, there’s note that in the learning process students receive most information from teacher (teacher centered), so the effect forward to student learning activity and material mastery are still not optimal yet. One of the efforts to maximize it are using TGT models learning and Flash Card media. The study aimed at inflence of TGT models with Flash Card media towards learning students’ activity and material mastery. This study uses design pretest-posttest not equivalent model with X3as experiments’ class (27 students) and X1 as controls’ class (30 students) was elected in cluster random sampling technique. The data of this study was obtained from the pretest and posttest, observation sheet and questionnaire of students respon about this study. Data analyzed using a t-test on the SPSS17 program.The results showed that average percentage of students learning activities in all aspect that observed in experiment class (77,62 %) was higher than control class (62,78 %), with an average N-Gain of material mastery on 65,89 % in experimental and control class on 38,65 %. In addition, 27 students was pleased to learn the matter of virus by using TGT models and Flash Card media. Thus, the used of TGT models and Flash Cards have influation toward students learning activities and material mastery of Virus as significantly.Keywords: TGT, Flash Card, material mastery, student learning activity, Virus.